2023
DOI: 10.1002/smll.202308297
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Dendrites Issue in All Solid‐State Batteries with Inorganic Electrolyte: Mechanism, Detection and Suppression Strategies

Tianrui Sun,
Qi Liang,
Sizhe Wang
et al.

Abstract: All solid‐state batteries (ASSBs) are regarded as one of the promising next‐generation energy storage devices due to their expected high energy density and capacity. However, failures due to unrestricted growth of lithium dendrites (LDs) have been a critical problem. Moreover, the understanding of dendrite growth inside solid‐state electrolytes is limited. Since the dendrite process is a multi‐physical field coupled process, including electrical, chemical, and mechanical factors, no definitive conclusion can s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 207 publications
0
3
0
Order By: Relevance
“…All-solid-state lithium-ion batteries (ASSLIBs) employing inorganic solid electrolytes (SEs) are acknowledged to enable a more stable (electro)­chemo-mechanical environment for those volume-changing electrode materials than liquid LIBs. For instance, SEs cannot freely flow to wet the newly exposed electrode interfaces, which favors stable SEI formation. Among all investigated SEs, sulfide electrolytes exhibit favorable mechanical ductility and the highest room-temperature ionic conductivity comparable to or exceeding liquid electrolytes. , Recent advances have witnessed excellent compatibility of alloy-type anodes with sulfide SEs. Some typical alloy anodes (e.g., Si, Al, or their lithiated forms) used in sulfide ASSLIBs have achieved far better long-term cycling stability than liquid LIBs. Based on theoretical estimation, McDowell et al have identified that both gravimetric/volumetric energy densities of ASSLIBs with some alloy anodes are far beyond those of commercial graphite LIBs, even comparable to those evaluated of the Li-metal batteries using excess Li …”
Section: Introductionmentioning
confidence: 99%
“…All-solid-state lithium-ion batteries (ASSLIBs) employing inorganic solid electrolytes (SEs) are acknowledged to enable a more stable (electro)­chemo-mechanical environment for those volume-changing electrode materials than liquid LIBs. For instance, SEs cannot freely flow to wet the newly exposed electrode interfaces, which favors stable SEI formation. Among all investigated SEs, sulfide electrolytes exhibit favorable mechanical ductility and the highest room-temperature ionic conductivity comparable to or exceeding liquid electrolytes. , Recent advances have witnessed excellent compatibility of alloy-type anodes with sulfide SEs. Some typical alloy anodes (e.g., Si, Al, or their lithiated forms) used in sulfide ASSLIBs have achieved far better long-term cycling stability than liquid LIBs. Based on theoretical estimation, McDowell et al have identified that both gravimetric/volumetric energy densities of ASSLIBs with some alloy anodes are far beyond those of commercial graphite LIBs, even comparable to those evaluated of the Li-metal batteries using excess Li …”
Section: Introductionmentioning
confidence: 99%
“…Although much progress has been made in recent years in lithium dendrite suppression strategies for solid electrolytes (SEs), the lithium dendrite resistance still needs to improve, and more efficient strategies are needed to address this issue. 35 The study of the growth mechanism of lithium dendrites not only has significant scientific significance but also contributes to the development of strategies to suppress lithium dendrite growth.…”
mentioning
confidence: 99%
“…On the other hand, some studies suggest that the growth of lithium dendrites in solid electrolytes is an electrochemical process, which involves the reduction of lithium ions to lithium metal through the transportation of electrons in the solid electrolyte. , Further evidence shows that electronic insulation layers could effectively suppress the growth of lithium dendrites, which align with the electrochemical growth theory. , The construction of an electronic-insulated solid–electrolyte interphase (SEI) layer on the surface of a lithium metal negative electrode and the reconstruction of LLZO grain boundaries using an electronic-insulated polymer to suppress the growth of lithium dendrites also indicate that the growth of lithium dendrites is an electrochemical process. , Besides, the metal interlayer and alloying method, mechanical compensation, surface patterning, and adjustment of the grain boundary area can also suppress the growth of lithium dendrites when the micromechanism is unclear. Although much progress has been made in recent years in lithium dendrite suppression strategies for solid electrolytes (SEs), the lithium dendrite resistance still needs to improve, and more efficient strategies are needed to address this issue . The study of the growth mechanism of lithium dendrites not only has significant scientific significance but also contributes to the development of strategies to suppress lithium dendrite growth.…”
mentioning
confidence: 99%